Therapeutic targeting of the pathological triad of extrasynaptic NMDA receptor signaling in neurodegenerations - Bading, Hilmar (Journal of experimental medicine, 2017)
Activation of extrasynaptic N-methyl-d-aspartate (NMDA) receptors causes neurodegeneration and cell death. The disease mechanism involves a pathological triad consisting of mitochondrial dysfunction, loss of integrity of neuronal structures and connectivity, and disruption of excitation-transcription coupling caused by CREB (cyclic adenosine monophosphate-responsive element-binding protein) shut-off and nuclear accumulation of class IIa histone deacetylases. Interdependency within the triad fuels an accelerating disease progression that culminates in failure of mitochondrial energy production and cell loss. Both acute and slowly progressive neurodegenerative conditions, including stroke, Alzheimer’s disease, amyotrophic lateral sclerosis, and Huntington’s disease, share increased death signaling by extrasynaptic NMDA receptors caused by elevated extracellular glutamate concentrations or relocalization of NMDA receptors to extrasynaptic sites. Six areas of therapeutic objectives are defined, based on which a broadly applicable combination therapy is proposed to combat the pathological triad of extrasynaptic NMDA receptor signaling that is common to many neurodegenerative diseases.